Comparing tools of balance tests in assessing balance of middle-aged women with or without exercises - Nawanto Agung Prastowo; Michelle Olivia Budiarta; Kidyarto Suryawinata; Ignatio Rika Haryono (JKKI : Jurnal Kedokteran dan Kesehatan Indonesia, 2020)
Background: Fall risks among middle-aged women are relatively high. However, there is a lack of studies on tools of balance tests and their accuracy among middle-aged women. Objective: The aim of this study is to compare three tools of balance tests to predict falls of middle-aged women who exercise regularly and who do not. Methods: Eighty-five middle-aged women (50-64 years old) were included in this study, and 40 women of them (47.1%) exercised regularly. The Berg Balance Scale (BBS), Timed Up and Go Test (TUG), and 30-second Chair Stand Test (30-s CST) were the tools examined in this study. The numerical data of this study were analyzed by using a Mann-Whitney test. Those were significant if p<0.05. Accuracy of the tools of balance tests was evaluated by using Receiver Operating Characteristic (ROC) curve. Area under the curve (AUC) was significant if =0.70.Results: Based on this study, the middle-aged women (EG) indicated lower score of TU than sedentary (SG) test (6.9 ± 0.9 vs 8.3 ± 1.7, p = <0.000), and higher score of 30-s than sedentary (SG) test (20.1 ± 3.6 vs 17.2 ± 5.6, p = 0.026). Three participants (3.53%) reported history of falls. The TUG test had better accuracy to predict the falls (AUC 0.922, 95% CI 0.840 - 1.005, sensitivity 1.00, specificity 0.84, p=0.013). Mostly, the participants (˜70%) preferred to practice Tai Chi and Yoga. Conclusion: The middle-aged women who exercised could have a better score of the balance tests, and the TUG test could predict falls of them.